2015
DOI: 10.1515/pjvs-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral administration of commercial gold nanocolloid on peripheral blood leukocytes in mice

Abstract: During the last few decades, owing to their unique properties, gold nanoparticles (AuNPs) have found numerous biomedical applications. Studies on rodents prove that AuNPs entering an organism easily reach the bloodstream and undergo wide tissue distribution. The presence of nanoparticles inside blood and bone marrow cells of exposed animals may implicate its influence on hematopoesis and the functions of peripheral blood leukocytes.The aim of this study was to determine the effect of oral administration of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Further, in vivo GNP effects are dose-dependent. In particular, Małaczewska 59,60 demonstrated that mice, after being orally administered with GNPs, showed an increased activity of phagocytes and some changes in the lymphocyte phenotypes, i.e. , an increased percentage of B and CD4+/CD8+ double positive T cells.…”
Section: Interaction Of Gold Nanoparticles With Immune Cellsmentioning
confidence: 99%
“…Further, in vivo GNP effects are dose-dependent. In particular, Małaczewska 59,60 demonstrated that mice, after being orally administered with GNPs, showed an increased activity of phagocytes and some changes in the lymphocyte phenotypes, i.e. , an increased percentage of B and CD4+/CD8+ double positive T cells.…”
Section: Interaction Of Gold Nanoparticles With Immune Cellsmentioning
confidence: 99%
“…In accordance with our findings, Bastús et al 39 found that AuNPs enhanced the induction of proinflammatory cytokines such as TNF-α, IL-1, and IL-6 in macrophages. Malaczewska 40 found that mice given AuNPs orally had increased phagocyte activity and some changes in lymphocyte phenotypes, including a higher percentage of B and CD4+/CD8+ double-positive T cells. The lowest dose increased the synthesis of the proinflammatory cytokines IL-1, IL-2, IL-6, and TNF-α, and had a proinflammatory or immune-stimulating effect.…”
Section: Discussionmentioning
confidence: 99%
“…Malaczewska [58] demonstrated that mice, after being orally administered with GNPs showed increased the phagocytes activity and the percentage of both B and CD4+/CD8+ double-positive T cells. On the other hand, the effect of the highest dose can be considered pro-inflammatory and immunotoxic, because of the stimulated pro-inflammatory cytokine as TNF, IL-2 and IL-6 synthesis was accompanied by a drastic decline in the proliferative activity of lymphocytes and extensive pathological lymphocytolysis and lymphocytic depletion in different lymphoid organs [59]. Several recent publications have been reported the dose-dependent GNPs induced changes (both increasing and decreasing) in the number of the immune cells [60,61].…”
Section: Discussionmentioning
confidence: 99%